Numerical modelling of high efficiency GaAs/Si solar cell using various TLARC - Aminuddinr, Syahzanani Afiqah; Yahaya Bermakai, Madhiyah (2024)
The problem focuses on the efficiency of gallium arsenide/silicon (GaAs/Si) solar cells, which are hindered by high reflectivity, resulting in lower short circuit currents. To address this issue, various anti-reflection coatings, such as triple-layer antireflection coatings (TLARCs), are being explored to reduce reflection losses and improve the efficiency of GaAs/Si solar cells. The objectives are to develop a numerical model for GaAs/Si solar cells and evaluate the efficiency of TLARC materials compatible with GaAs/Si solar cells. The research methodology involves designing and optimising triple anti-reflection coatings on silicon solar cells using the PC1D simulation technique. Five different TLARC materials are used in this study. The significant output is to improve solar cell technology, making solar power a more practical and sustainable energy source. It also aids in climate change mitigation by lowering greenhouse gas emissions and promoting clean energy solutions. The study employs PC1D simulation software to model and optimise TLARCs on GaAs/Si solar cells, analysing simulation results to determine optimal configurations. The SiO2/MgF2/Si3N4 TLARC combination has proven to be especially effective, reaching a peak efficiency of 19.10%, which is close to the current industrial photovoltaic system.